RAHASIA HEKSAGONAL PADA SARANG LEBAH MADU (PANDANGAN SAINS DAN ISLAM) - Hilda, Lelya (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2016)
Bees are distinguished colony as Allah SWT has dedicated a surah in Al Qur-an with the name of An-Nah.Â  They live in colonies to produce honey and build a hexagonal-shaped nest with precision from the outside till the inside. Hexagonal is the most effective geometry to accommodate maximum quantityÂ  of honey and minimizing the ingredients. They even produce honey so much more than the required quantity. This phenomenon has taught us to take the good from good sources and to manage them in a good way, so as to produce something good and beneficial for others.